Relapsing Ipsilateral Vestibular Neuritis - Duilio Emiliano De Schutter; Nicolás Pérez Fernández (Case Reports in Otolaryngology)
In 2013, a 70-year-old male was admitted with an acute episode of vertigo, nausea, and vomiting with duration of one day. The patient’s background included prehypertension, vitiligo, left ventricular hypertrophy, and Sjögren's syndrome. He denied any previous episode of vertigo or migraine manifestations. Neither hearing loss nor tinnitus or otorrhea was detected at the time of evaluation. No neurological symptoms were found. There was a left-beating spontaneous nystagmus Grade 3. The patient could stand still and walk on his own with some help without falling. Day 1 vHIT showed a significant reduction in VOR gain and refixation saccades after head impulses were delivered in the planes of the right anterior and horizontal semicircular canals. MRI showed no significant findings. He was treated with steroids. A vHIT performed 14 days later showed recovery of gains and no refixation saccades. In 2015, the patient had a new episode of acute vertigo. The clinical examination was similar, and the vHIT revealed a new drop of right superior and lateral canal gains. Cervical and ocular VEMPs were performed, and no significant asymmetry was detected. Serum PCR for herpes viruses resulted negative. Contrast MRI was performed without relevant brain findings.